Response of geochemical characteristics of organic-rich shale of Longmaxi formation to the sedimentary environment in the Neijiang-Rongchang area, Sichuan Basin, China - Yang, Licheng; Hu, Yi; Yang, Xinrui; Zhang, Lianghua; Tang, Wen; Liu, Dongxi; Li, Huilin; Wen, Qibing; Xie, Lin; Wang, Xingzhi; Kang, Jiahao; Xi, Zhidian; et al. (Frontiers in Earth Science, 2025)
The Lower Paleozoic (Upper Ordovician–Silurian), a globally deposited organic-rich shale, is one of the most prevalent source rocks worldwide. However, the origin of these shales remains uncertain. Here, this study reports geological and geochemical findings that present novel evidence for the origin of these shales. The mineral composition of Lower Silurian Longmaxi shale is dominated by quartz (average: 53.76%) and clay minerals (average: 33.37%). It constitutes a small amount of feldspar, calcite, dolomite, and pyrite. The Longmaxi Formation shale has high organic matter content (more than 2% on average). According to the geochemical indices, such as V/(V + Ni), Ni/Co., U/Th and Mo/total organic carbon (TOC), the Longmaxi Formation shale was deposited in the marine basin environment stranded by the sulphidation of anoxic water. Sensitive elements, such as Ba, Mo, P and Ti, indicate that although the primary productivity of the Longmaxi Formation shale remains low, it still has excellent source rock potential because of superior preservation conditions. A comparative study is conducted with the Lower Silurian hot shale in other parts of the world, it is found that the enrichment of organic matter in the Longmaxi Formation is controlled by high primary productivity (nutrients brought by upwelling) and strong preservation conditions (hypoxia caused by stratified water body), which subverts the traditional cognition of single main controlling factor. The organic matter enrichment of the Lower Silurian thermal shale has a ' productivity-preservation condition ' trade-off mechanism: low latitudes (such as North Africa) are dominated by high productivity. The middle and high latitudes (such as South China) are dominated by strong preservation conditions (limited basin sulfidation). It provides theoretical basis and motivation for future research and effectively guides the exploration and development of unconventional shale gas.